Green closed-loop cathode regeneration from spent NMC-based lithium-ion batteries through bioleaching - Do, Minh Phuong (2022)
Addressing the growing volume of end-of-life lithium-ion battery (LIB) waste is one of the global challenges in tackling the electronic waste problem. In this study, the regeneration of LiNi0.3Co0.3Mn0.3O2 (NMC111) and Li- Ni0.6Co0.2Mn0.2O2 (NMC622) cathode-active materials from end of- life LIBs was accomplished through an environmentally friendly bioleaching process. In the bioleaching process mediated by Acidithiobacillus ferrooxidans, 85.5% of Ni, 91.8% of Mn, 90.4% of Co, and 89.9% of Li were leached out from NMC-based spent LIBs in 6 h at a pulp density of 100 g/L. One of the challenges in bioleaching-based metal recovery is the presence of impurities, including Cu, Al, and Fe (excess Fe3+ and Fe2+ from bacterial nutrients). The impurity removal was performed by air oxidation and pH adjustment without substantial losses of other metallic ions. Thereafter, ammonium oxalate coprecipitation effectively recovered the transition metal ions as metal oxalates from the bioleaching liquor. NMC111 and NMC622 were regenerated from the coprecipitated product. The electrochemical stability of the regenerated NMC111 and NMC622 was comparable to commercial NMC (∼85% of capacity retention after 50 cycles at 100 mA g−1). This regeneration approach appears promising in LIB recycling for long-term industrial development.